Microlenses arrays: Fabrication, materials, and applications. Issue 11 (14th May 2021) - Cai, Shuxiang; Sun, Yalin; Chu, Honghui; Yang, Wenguang; Yu, Haibo; Liu, Lianqing
Abstract: Microlenses have become an indispensable optical element in many optical systems. The advancement of technology has led to a wider variety of microlenses fabrication methods, but these methods suffer from, more or less, some limitations. In this article, we review the manufacturing technology of microlenses from the direct and indirect perspectives. First, we present several fabrication methods and their advantages and disadvantages are discussed. Then, we discuss the commonly used materials for fabricating microlenses and the applications of microlenses in various fields. Finally, we point out the prospects for the future development of microlenses and their fabrication methods. Abstract : Manufacturing technology of microlenses from the direct and indirect perspectives is reviewed. The commonly used materials for fabricating microlenses and the applications of microlenses in imaging are reviewed. The future development of microlenses and their fabrication methods are summarized.